Prognostic effect of serum BDNF levels in late-life depression: Moderated by childhood trauma and SSRI usage?. (May 2019) - Dimitriadis, M.; van den Brink, R.H.S.; Comijs, H.C.; Oude Voshaar, R.C
Highlights: Actual BDNF serum levels do not predict remission of late-life depression, independent of childhood trauma and SSRI usage. BDNF predicts remission of late-life depression among traumatized non-SSRI users. BDNF predicts remission of late-life depression among non-traumatized SSRI users. The responsiveness of the neurotrophic system might be permanently reduced ('blunted') by childhood trauma. The responsiveness of the neurotrophic system to SSRIs may correlate with remission of late-life depression. Abstract: Background: Brain-derived neurotrophic factor (BDNF) levels decline during depression and normalise after remission, although studies in older patient samples are inconsistent. Whether BDNF serum levels predict depression remission is unclear. We hypothesize that the predictive value of serum BDNF levels in late-life depression is moderated by selective serotonin reuptake inhibitors (SSRI) usage and early traumatization. Methods: Our study sample was a subset of the Netherlands Study of Depression in Older persons (NESDO), a prospective cohort study. It consisted of 267 older persons with a diagnosis of depression, for which follow-up data were available. Depression diagnosis was assessed at baseline and follow up using a structured diagnostic interview (Composite International Diagnostic Interview (CIDI), volume2.1). Logistic regression was performed (adjusted for covariates) with remission of depression after two years as the dependent variable and baseline BDNF serum levels, childhood traumatization and SSRI use as independent variables. Results - The mean age of the subjects was 70.7 years, 65.6% of them were female, their mean BDNF level was 7.7 ng/ml, 80 (30.0%) of them were traumatised in their childhood, 71 (26.6%) used SSRIs and 136 (50.9%) no longer had a depressive disorder at the two year follow up. The predictive value of BDNF serum levels was conditional on traumatization and SSRI usage (threeway interaction p = .010). Higher BDNF serum levels predicted remission in traumatized depressed patients without SSRI usage (OR = 1.17, 95% C.I.: 1.00–1.36; p = .048) and in non-traumatized depressed patients who used SSRIs (OR = 1.17, 95% C.I.: 1.00–1.36; p = .052), but not in the other two subgroups. Conclusion: The association between BDNF serum levels and the course of late-life depression seems to depend on SSRI use and childhood trauma. Based on these results, we hypothesize that childhood trauma may permanently reduce ('blunt') the responsiveness of the neurotrophic system to SSRI usage, and that this responsiveness might be more important for depression course than the actual BDNF serum levels.